Evaluating The Extent Of Applying Internal Marketing Strategies In Private Commercial Banks A Field Study In The Branches Of The Syrian Commercial Banks In The Damascus Governorate - Mourhij, Mounzer; Al-Deen, Bassel alaa (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aimed to evaluate the internal marketing situation in the private commercial banks in Damascus Governorate. The researchers identified five internal marketing strategies in these banks, which included clarity of role, training and staff empowerment, Stimulus and employee relations. The researchers distributed a questionnaire to a random sample of 120 workers, each containing 35 questions, measuring the five strategies of internal marketing, testing the stability of the scale used on the Cronbach’s Alpha coefficient, using t-test for one sample to test hypotheses, The researchers found that there were high levels of internal marketing strategies (clarity of role, Stimulate employees, employee relationships), Where the differences were significant between the average answers for each of the three internal marketing strategies and the average neutrality of the scale used. هدف هذا البحث إلى تقويم واقع التسويق الداخلي في المصارف التجارية الخاصة في محافظة دمشق، حيث قام الباحثان بتحديد خمس استراتيجيات للتسويق الداخلي في تلك المصارف, شملت كل من وضوح الدور، والتدريب, وتمكين الموظفين، والتحفيز, والعلاقات بين الموظفين. وقد قام الباحثان بتوزيع استبانة على عينة عشوائية من الموظفين بلغت /120/مفردة، وتضمنت كل استبانة/35/ عبارة، تقيس الاستراتيجيات الخمس من التسويق الداخلي، وقاما باختبار مدى ثبات المقياس المستخدم اعتماداً على معامل ألفا كرونباخ، واستخدما اختبار - tستودينت لعينة واحدة لاختبار الفرضيات، وقد توصل الباحثان إلى نتائج تبيّن وجود مستويات عالية من استراتيجيات التسويق الداخلي (وضوح الدور, تحفيز الموظفين, العلاقات بين الموظفين), حيث كانت الفروق جوهرية بين متوسط الاجابات التي تخص كل استراتيجية من استراتيجيات التسويق الداخلي الثلاث ومتوسط الحياد للمقياس المستخدم.